Methane oxidation in presence of sulfur dioxide - Mantashyan, A. A.; H. Wang; A. M. Avetisyan; E. M. Makaryan (ՀՀ ԳԱԱ հրատ.)
The oxidation of methane in presence of sulphurous gas (SO2) addition was studied experimentally. The experiments were conducted in a static reactor at temperatures of 728 and 786 K, and for mixture of CH4:O2 = 1:2 at a pressure of 117 Torr with varying amount of SO2 addition. Փորձնականորեն ուսումնասիրվել է մեթանի օքսիդացման պրոցեսը ծծմբային գազի` SO2, հավելումների առկայությամբ: Փորձերը իրականացվել են ստատիկ պայմաններում, փակ անոթում, երկու ջերմաստիճաններում` T=728 և 786 K, CH4:O2=1:2 բաղադրությամբ խառնուրդի, P=117 մմ ս.ս. ճնշման և SO2-ի տարբեր հավելումների դեպքում: Экспериментально изучено окисление метана в присутствии добавок сернистого газа (SO2). Эксперименты проводились в статических условиях в замкнутом сосуде при двух температурах: 728 и 786 К, для смеси состава СН4:О2=1:2 при Р=117 Торр и различных добавках SO2.
Keywords: Physical Chemistry